Clinicopathological features and prognostic factors of malignant melanoma: A retrospective analysis of thai patients in ramathibodi hospital - Patlada Ingkaninanda (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To present the clinicopathological characteristics of cutaneous melanoma in Thai patients and to define the possible clinicopathological prognostic factors. Material and Method: A retrospective study of primary cutaneous melanoma in Thai patients in Ramathibodi Hospital between January 2007 and December 2012 was conducted. All medical records and skin biopsies were reviewed for demographic data and histopathological features. Univariate and multivariate analysis for overall survival, and prognostic factors, according to clinical and histopathological features were performed. Results: Fourty-three patients with pathologically confirmed primary cutaneous melanoma were identified and reviewed. The median age of onset was 58 years, with male:female ratio was 1:1.05. Acral lentiginous melanoma (ALM) was the most common type (76.7%). The majority of patients had clinical stage II (56.1%). Histologically, the median tumor thickness was 2.9 mm, 88.2% had Clark’s level IV and V, 47.1% were ulcerated, and 76.5% had dermal mitotic rate of ≥1 mitoses/mm2. The 5-year overall survival rates was 38.3%. Univariate analysis demonstrated that clinical stage IV, Breslow’s thickness of >3 mm, and dermal mitotic rate of ≥3 mitoses/mm2 were bad prognostic factors. Multivariate analysis demonstrated that advanced clinical staging (stage III and IV), Breslow’s thickness of >3 mm, ulceration, palmoplantar or subungual site, and histologic subtype of ALM were the independent risk factors for poor prognosis. Conclusion: Most patients with cutaneous melanoma in Thai patients had the histologic subtype of ALM, and were diagnosed with locally advanced disease (stage II). The prognosis depends on clinical staging, Breslow’s thickness, ulceration, primary location of tumor, and histologic subtype.